EFFECTIVENESS OF USE OF VILLAGE FUNDS IN BANGKA BELITUNG ISLANDS PROVINCE - Julia, Julia; Fahria, Izma; Bahri, Alim (Universitas Bangka Belitung, 2023)
This study aims to determine the effectiveness of village funds in supporting village development in the Bangka Belitung Archipelago Province. The type of research used in this study is quantitative research by comparing targets and realization from 2018-2022 and guidelines for the effectiveness category of using funds using the regulations of the Ministry of Home Affairs of the Republic of Indonesia. From the results of the Village Fund effectiveness test in the Bangka Belitung Islands Province, it shows that the average level of effectiveness is 99.91%, included in the quite effective category. With the highest level of effectiveness, which is almost 100%, it is found in Bangka Regency. This indicates that the management of Village Fund Allocations in the Bangka Belitung Islands Province is carried out optimally. Because the realization of the Village Fund Allocation obtained has reached the revenue target set in the Village Fund Allocation budget.